Traumatic avulsion of the tricuspid valve after gas bottle explosion - Tedoldi, Francesca (Echo Res Pract, 2016)
We present a very rare example of chronic right heart failure caused by torrent tricuspid regurgitation. Massive right heart dilatation and severe tricuspid regurgitation due to avulsion of the tricuspid valve apparatus occurred as a result of a blunt chest trauma following the explosion of a gas bottle 20 years before admission, when the patient was a young man in Vietnam. After this incident, the patient went through a phase of severe illness, which can retrospectively be identified as an acute right heart decompensation with malaise, ankle edema, and dyspnea. Blunt chest trauma caused by explosives leading to valvular dysfunction has not been reported in the literature so far. It is remarkable that the patient not only survived this trauma, but had been managing his chronic heart failure well without medication for over 20 years. LEARNING POINTS: Thorough clinical and physical examination remains the key to identifying patients with relevant valvulopathies. With good acoustic windows, TTE is superior to TEE in visualizing the right heart. Traumatic avulsion of valve apparatus is a rare but potentially life-threatening complication of blunt chest trauma and must be actively sought for. Transthoracic echocardiography remains the method of choice in these patients.